The impact of investor protection law on takeovers: The case of leveraged buyouts - CAO, Jerry (Institutional Knowledge at Singapore Management University, 2008)
This paper examines the impact of investor protection on the value creation of LBOs. We find that target shareholders’ wealth gain is higher in countries with better investor protection. The impact of investor protection on takeover premium is larger for LBO than non-LBO transactions. We also find evidence suggesting that club LBOs are not priced lower than non-club deals after accounting for endogeneity problem. These results suggest that investor protection law may act as an important safeguard for minority shareholders in LBO transactions.